2018
DOI: 10.1038/s41598-018-26085-1
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Nerve Enlargement and Neuratrophy Detected by Ultrasonography in Leprosy Patients

Abstract: The purpose of this study was to evaluate peripheral neural impairment in leprosy patients by ultrasonography (US). The cross-sectional areas (CSAs) of the median (M), ulnar (U) and common fibular (CF) nerves were compared in 71 leprosy patients and 29 healthy controls, and the data were analyzed between the leprosy, multibacillary (MB)/paucibacillary (PB), reaction (R)/no reaction (NR), disability (D)/no disability (ND), and longer/shorter duration groups after treatment. We found that for the nerves located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 17 publications
0
12
0
4
Order By: Relevance
“…In another study, the mean CSA of the median nerve was 14.7 ± 11.6 mm 2 2 . In a study by Chen et al, 17 a combination of enlarged CSA of nerves in the upper limbs and atrophy of lower limb nerves was noted. While one study reported increased CSA in paucibacillary as compared to multibacillary leprosy, another study reported the contrary 3,17 .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In another study, the mean CSA of the median nerve was 14.7 ± 11.6 mm 2 2 . In a study by Chen et al, 17 a combination of enlarged CSA of nerves in the upper limbs and atrophy of lower limb nerves was noted. While one study reported increased CSA in paucibacillary as compared to multibacillary leprosy, another study reported the contrary 3,17 .…”
Section: Discussionmentioning
confidence: 81%
“…In a study by Chen et al, 17 a combination of enlarged CSA of nerves in the upper limbs and atrophy of lower limb nerves was noted. While one study reported increased CSA in paucibacillary as compared to multibacillary leprosy, another study reported the contrary 3,17 . Nerve enlargement has been reported to be more pronounced among those in reaction and longer disease duration 17,20 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The authors suggest that nerve enlargement and atrophy may coexist in the pathophysiology of neuropathy associated with leprosy. 68 Another group found that the magnitude of nerve thickening is greater in MB and in patients with reactions. 69 A prospective case-control study evaluated the ulnar nerves of 48 patients diagnosed with leprosy at three locations close to the elbow, compared with 60 clinically normal ulnar nerves.…”
Section: Diagnosismentioning
confidence: 99%